A case of streptococcal surgical site infection following Mohs surgery - Kami B. Lowery; John J. Kohorst; C. Helen Malone; Ikue Shimizu (PAGEPress Publications, 2020)
Group A β-hemolytic Streptococcal (GAS) cellulitis is an uncommon surgical site infection that presents with rapid onset of pain and swelling in the first few days after a procedure. Unlike staphylococcal cellulitis, GAS cellulitis lacks purulence and spreading erythema. The absence of these classic signs may delay the diagnosis of GAS cellulitis and lead to severe complications. We present the case of an immunosuppressed 49-year-old patient who developed swelling and severe pain at his incision site two days after undergoing Mohs micrographic surgery on his forehead. He was clinically diagnosed with GAS cellulitis and recovered with intravenous antibiotics. Unfortunately, there is a paucity of information about GAS cellulitis in the dermatologic literature and clinicians need to recognize and aggressively treat this rare but serious complication of Mohs micrographic surgery.